A Comparative Study of Response and Toxicity between Weekly Cisplatin plus Radiotherapy Versus Weekly Carboplatin plus Radiotherapy in Locally Advanced Squamous Cell Carcinoma of Head-Neck - Ahmed Riad, Mahfujul (Journal of Enam Medical College, 2024)
Background: Head and neck cancers are the common cancers in developing countries. Concurrent chemoradiotherapy is the treatment of choice for locally advanced stage III to IVB squamous cell carcinoma of head and neck. Carboplatin possesses comparable treatment response and better tolerability than cisplatin. Objectives: The study has been conducted to elucidate the comparable efficacy and favorable toxicity profile of carboplatin instead of cisplatin. Materials and Methods: This study was conducted at National Institute of Cancer Research and Hospital, Dhaka from March 2018 to March 2019 over 60 patients divided into 2 groups. Group A patients received cisplatin 40 mg/ m2 and group B patients received carboplatin AUC 2 along with 66 Gy in 33 fractions of radiation. Treatment response and toxicities was evaluated periodically. Results: Total 12 (40%) patients of arm A and 8 (26.7%) patients of arm B had complete response, 10 (33.4%) patients of arm A and 12 (40%) patients of arm B had partial response, 6 (20%) patients of arm A and 3 (10%) patients of arm B had stable disease and 2 (6.7%) patients of arm A and 7 (23.3%) patients of arm B developed progressive disease. Cisplatin showed more vomiting (57.6%), nephrotoxicity (55.2%), ototoxicity (33.9%) and neurotoxicity (35.4%). On the other hand, carboplatin showed more myelosuppression (anemia 43.6%, neutropenia 44.5% and thrombocytopenia 64.3%). Conclusion: This study concluded that, both cisplatin and carboplatin have comparable efficacy and carboplatin has favorable safety profile. J Enam Med Col 2021; 11(3): 173−179